A randomized controlled trial of nebulized surfactant for the treatment of severe COVID-19 in adults (COVSurf trial) - Ahilanandan Dushianthan; Howard W. Clark; David Brealey; Danny Pratt; James B. Fink; Jens Madsen; Helen Moyses; Lewis Matthews; Tracy Hussell; Ratko Djukanovic; Martin Feelisch; Anthony D. Postle; et al. (Scientific Reports, 2023)
Abstract SARS-CoV-2 directly targets alveolar epithelial cells and can lead to surfactant deficiency. Early reports suggested surfactant replacement may be effective in improving outcomes. The aim of the study to assess the feasibility and efficacy of nebulized surfactant in mechanically ventilated COVID-19 patients. Patients were randomly assigned to receive open-labelled bovine nebulized surfactant or control (ratio 3-surfactant: 2-control). This was an exploratory dose–response study starting with 1080 mg of surfactant delivered at 3 time points (0, 8 and 24 h). After completion of 10 patients, the dose was reduced to 540 mg, and the frequency of nebulization was increased to 5/6 time points (0, 12, 24, 36, 48, and an optional 72 h) on the advice of the Trial Steering Committee. The co-primary outcomes were improvement in oxygenation (change in PaO2/FiO2 ratio) and ventilation index at 48 h. 20 patients were recruited (12 surfactant and 8 controls). Demographic and clinical characteristics were similar between groups at presentation. Nebulized surfactant administration was feasible. There was no significant improvement in oxygenation at 48 h overall. There were also no differences in secondary outcomes or adverse events. Nebulized surfactant administration is feasible in mechanically ventilated patients with COVID-19 but did not improve measures of oxygenation or ventilation.